Neutrophils negatively control IL-17A-producing γδ T cell frequencies in a contact-dependent manner under physiological conditions - Yu, Xinhua; Yue, Xiaoyang; Tchudjin Magatsin, Junie D.; Marwitz, Sebastian; Behrends, Jochen; Goldmann, Torsten; Opferman, Joseph T.; Kasper, Brigitte; Petersen, Frank (Frontiers in Immunology, 2025)
BackgroundIn addition to serving as the primary effector cells against infections, neutrophils have been implicated in the regulation of both innate and adaptive immunity. In this study, we aimed to investigate the role of neutrophils in the regulation of the immune system under physiological conditions.MethodsThe in vivo effect of neutrophils on the immune system was examined using neutropenic mice. The interaction between neutrophils and γδ T cells was investigated using an in vitro co-culture system.FindingsUnexpectedly, we observed an accumulation of γδ T cells in the cervical lymph nodes of neutropenic mice. Transcriptomic analysis revealed that these γδ T cells exhibited unique expression profiles of cell surface molecules and genes involved in defense responses. Further characterization indicated that the accumulated γδ T cells were IL-17 producing CD44+CD62L−CD27− memory cells. Additionally, in vitro experiments demonstrated that neutrophils could inhibit the function of IL-17A producing γδ T cells by inducing cell death in a contact-dependent manner.ConclusionThis present study demonstrates that neutrophils negatively regulate IL-17 producing γδ T cells under physiological conditions. Given that IL-17A is a critical cytokine for the recruitment of neutrophils to peripheral tissues, our study suggests that the crosstalk between neutrophils and IL-17A producing γδ T cells is a crucial mechanism for maintaining immune homeostasis under physiological conditions.